Delineate the quality of underground water for irrigation of north-western part of Pali district of Rajasthan - Kamlesh Choudhary; Yogesh Sharma; Ranjeet Singh (Annals of Agricultural Research, 2022)
The present study was undertaken at Swami Keswanand Rajasthan Agriculture University, Bikaner, Rajasthan during the year 2019-20. The pH and EC of irrigation water of north-western part of Pali district varied from 7.00 to 9.12 and 0.44 to 21.60 dS m-1, respectively. The SAR and RSC values of irrigation water ranged between 3.27 to 24.34 and 0.0 to 7.99 me L-1, respectively. About 4.22, 29.52, 65.06 and 1.20 per cent water samples had SAR < 5, 5-10, 10-20 and 20-30, respectively and about 84.94, 12.05, and 3.01 per cent water samples showed RSC < 2.5, 2.5-5.0 and 5.0-10.0 me L-1, respectively. The pHc, Adj. SAR and SSP values of irrigation water of the studied area ranged between 5.60 to 8.20, 4.91 to 74.52 and 48.68 to 90.67, respectively.